2009
DOI: 10.1209/0295-5075/87/27005
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric function and plasmons in graphene

Abstract: The electromagnetic response of graphene, expressed by the dielectric function, and the spectrum of collective excitations are studied as a function of wave vector and frequency. Our calculation is based on the full band structure, calculated within the tight-binding approximation. As a result, we find plasmons whose dispersion is similar to that obtained in the single-valley approximation by Dirac fermions. In contrast to the latter, however, we find a stronger damping of the plasmon modes due to inter-band a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 18 publications
4
77
1
Order By: Relevance
“…in agreement with earlier studies of the dynamical screening effects in graphene at RPA level, employing an approximate conic dispersion relation for electrons around the Dirac points 8,9 . Such a result has been confirmed also for a tight-binding band 10,37 , and is here generalized with the inclusion of LFE. The effect of spin-orbit interaction can be neglected, in the case of sufficiently large chemical potential 11 , as is here the case.…”
Section: Plasmonssupporting
confidence: 74%
“…in agreement with earlier studies of the dynamical screening effects in graphene at RPA level, employing an approximate conic dispersion relation for electrons around the Dirac points 8,9 . Such a result has been confirmed also for a tight-binding band 10,37 , and is here generalized with the inclusion of LFE. The effect of spin-orbit interaction can be neglected, in the case of sufficiently large chemical potential 11 , as is here the case.…”
Section: Plasmonssupporting
confidence: 74%
“…We calculate the 2D wave vector and frequency-dependent nonlocal-RPA conductivity σ = σ + iσ using a well-known expression for the real part [33,40],…”
Section: Theoretical Formalismmentioning
confidence: 99%
“…A rigorous description of these effects requires the inclusion of spatial dispersion (i.e., nonlocal effects, NLEs) in a realistic manner, which we achieve by adopting the random-phase approximation [30] (nonlocal-RPA) for monolayers of these three materials, using as input the single-electron wave functions obtained from a tight-binding (TB) parametrization of the valence band region [31,32]. Graphene and MoS 2 are nearly isotropic [33] in contrast to BP [15], which we explore for 2D optical wave vector q oriented along both X and Y directions. We compare the full nonlocal-RPA response with semianalytical results obtained in the local low-q limit (local-RPA), and more precisely, we present dispersion relations under a wide range of doping and heating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene, a material consisting of one monolayer of carbon atoms, provides unique properties, such as optical transparency, flexibility, high electron mobility and conductivity, which can be tuned by electrochemical potential via, for example, electrostatic gating, magnetic field or optical excitation [4][5][6]. It was theoretically shown that graphene supports surface plasmon polaritons in the terahertz and infrared ranges [7][8][9][10][11][12][13][14][15] and can be a building material for metamaterials, which provide a wider range of electromagnetic properties than continuous graphene. Therefore continuous and structured graphene allows for an ultimate terahertz radiation control resulting in functional devices [16], such as modulators [17][18][19], hyperlenses [20], tunable reflectors, filters, absorbers and polarizers [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%